Cyanobacterial Soil Surface Consortia Mediate N Cycle Processes in Agroecosystems - Peng, Xin; Bruns, Mary Ann (Frontiers in Environmental Science, 2019)
Recurrent cyanobacterial growth on soil surfaces in hydric climatic regimes has received less study than biological soil crusts (BSCs) of xeric biomes. We assessed the potential for cyanobacteria to perform important nitrogen (N) cycle processes during growth on N-fertilized soils of hydric regions by testing a microbial consortium (DG1) enriched from a local agricultural soil. The metagenome of DG1 had been shown by shotgun sequencing to consist of Cylindrospermum spp. and six additional bacterial genomes. We refer to DG1 and similar assemblages as soil surface consortia (SSCs) to distinguish them from classical BSCs. We evaluated the ability of DG1 to fix N2 in the presence of inorganic N by measuring biomass uptake of 15N2 during 7-d incubations in a controlled-atmosphere chamber in media containing 0, 0, 62, 124, or 247 mg L-1 NO3-N. After 7 d, mean 15N atom % excess in DG1 biomass was 0.0143, 0.0029, 0.0037, and 0.0038 at the four NO3-N concentrations, respectively. Mean 15N atom % excess in dead cell controls was not significantly larger than zero. Mean N2 fixation rates of 101.3, 18.9, 25.6, and 26.6 ug N g-1 dry biomass d-1, respectively, indicated that DG1 continued to fix N2 in the presence of NO3-N, but at rates fourfold to fivefold lower than in N-free medium. We also assessed the potential for the SSC to retain soil NO3-N by applying simulated rainfall to soil microcosms inoculated with three levels of DG1 and grown for 1, 3, and 7 d at varied NO3-N concentrations. Overall, inoculation resulted in 50-70% more soil N retained after rainfall (p < 0.001) compared to non-inoculated microcosms. The effect of establishment time was significant (p = 0.043). Since water infiltration rates through microcosms were not significantly affected, we inferred that SSC biomass absorbed and/or immobilized NO3-N. These results show how SSCs can modulate soil N, either by fixing more N2 under N-limited conditions or by immobilizing inorganic N when concentrations are higher. Thus, naturally occurring or intentionally inoculated SSCs represent potential renewable sources of biologically fixed N and means for soil stabilization and N retention in diverse agricultural systems.